(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
The lichen Xanthoparmelia mougeotii (Schaer.) Hale and five species of lichenicolous fungi are new to Ukraine: Homostegia piggotii (Berk. & Broome) P. Karst., Phoma ficuzzae Brackel, Sphaerellothecium parmeliae Diederich & Etayo, S. propinquellum (Nyl.) Cl. Roux & Triebel, and Syzygospora bachmannii Diederich & M.S. Christ. Lichens Melanelia disjuncta (Erichsen) Essl. and Lichenomphalia umbellifera (L.) Redhead, Lutzoni, Moucalvo et Vilgalys and lichenicolous fungius Lichenoconium lecanorae (Jaap) D. Hawksw. Are new to Crimea.